Present and future of Korean companies in the Argentine energy and infrastructure sector, Chinese presence and other challenges to overcome (2015)
This paper intends to carry out a study on the panorama facing the construction and energy companies of South Korea in Argentina. For this, an analysis is carried out on the operation of this type of companies from Korea at international level. In turn, a comparison is made about the operation of Chinese and Korean companies around the world. Finally, the biggest challenges of Korean companies that are in these sectors are exposed so that they can successfully enter the Argentine market